Sistem Klasterisasi Volume Sampah Organik di Kota Magelang menggunakan K-Means - Nurrohman, Muhamad; Maimunah, Maimunah; Sukmasetya, Pristi (LPPM POLITEKNIK LP3I BANDUNG, 2023)
Waste is one of the most serious problems faced by many regions. In Magelang City alone, 70 tons of waste is generated per day, and 60% of it is organic waste. Business sectors such as restaurants, culinary tours, markets, and hotels are high producers of organic waste. Organic waste can be utilized and sorted to be useful for maggot farmers, compost and biogas makers, but the lack of information about the source and availability of this waste is an obstacle for organic waste users and the Environmental Service. The purpose of this research is to assist the Environmental Agency in planning waste transportation, as well as making it easier for organic waste users to get information about the waste. In this study, the data used is waste volume data and data on the number of visitors and traders in hotels, markets, and street vendors in Magelang City, the data is then processed using the K-Means clustering algorithm. The data that has been processed produces the optimal number of clusters is 2, cluster 1 is a low waste volume producing category, while cluster 2 is a high waste volume producing category. After obtaining the clustering results using the K-Means algorithm, an evaluation of the results was carried out using the silhouette score method which resulted in a score value of 0.66, from the evaluation results it can be concluded that the application of the K-Means algorithm in clustering the volume of organic waste in Magelang City is quite good. With these results, it is hoped that it can help the Magelang City government, especially the Magelang City Environmental Agency, maggot cultivators, and other organic waste users to more easily obtain information about the availability of organic waste, which is expected to help reduce the volume of organic waste.